Yield benefit and ecophysiological processes behind the introgression of HaHB4 in a modern wheat in the Argentine Pampas - Ayala, Francisco; Curin, Facundo; Diaz-Zorita, Martín; Murguía, José; Montero Bulacio, Enrique; Portapila, Margarita; Otegui, María Elena; Chan, Raquel Lía; Gonzalez, Fernanda Gabriela (Elsevier, 2026)
Context or problem: Breeding for improved tolerance to water deficit is critical to mitigate the climate change impact on wheat yield. In 2020, Argentina approved the first wheat transformed with the sunflower HaHB4 gene (INDØØ412–7), which increased yield by 16 % compared to the non-transformed Cadenza under drought conditions. This benefit may have been overestimated, as Cadenza is a long cycle for the Pampas region. Additionally, the underlying physiological mechanisms of yield benefit, particularly those related to water use and water use efficiency, remain to be fully elucidated. Objective or research question: The aims of the study are (i) to quantify the yield advantage of HaHB4 in a modern, well-adapted cultivar and (ii) to elucidate the physiological processes involved in yield benefit, which is crucial for identifying optimal environments for this technology. Methods: An HaHB4-introgressed line of Algarrobo was compared with the conventional cultivar in a broad network of experiments comprising one greenhouse, with two irrigation levels, and 29 field environments within the Pampas region combining different locations (10), years (5) and treatments (sowing dates, irrigation). Results Under water deficit during the reproductive phase, the yield advantage of HaHB4 was 15 % in the greenhouse and 13 % in the field. HaHB4 improved the relative yield by 0.06–0.08 % per mm of water deficit, also responding positively to moderate heat stress (∑Tmax > 30 °C ∼40–60 °Cd). The enhanced water use and water use efficiency conferred by HaHB4, allowed for maintaining biomass and yield under water deficit. Conclusions: The hypothesis of an initial overestimation of HaHB4 benefits can be rejected because in the modern Algarrobo cultivar it showed a similar benefit as in Cadenza. In areas prone to drought combined with heat stress, the introgression of HaHB4 in modern cultivars would enhance yield stability by improving water-limited yield. This may have a great impact on productivity in rainfed cropping systems, like most of the wheat-producing areas around the world.